Effect of rhizobium inoculation on nodulation and yield of chickpea in Calcareous soil (Bangladesh Journal of Agricultural Research, 2009)
Two field experiments were carried out during two consecutive rabi seasons of 2002-03 and 2003-2004 at Farming System Research Site, Chabbish Nagar, Rajshahi (AEZ 11) with a view to assessing the effect of Rhizobium inoculation on four varieties of chickpea viz., BARI Chola-3, BARI Chola-4, BARI Chola-5 and BART Chola-6. Each variety was tested with and without Rhizobium inoculation. Each plot received basal application of 22 kg P/ha as TSP, 42 kg K/ha as MOP, 20 kg S/ha as gypsum and 5 kg Zn/ha as zinc oxide. Peat based rhizohial inoculurn (Rhizohium strain RCa-220) @ 1.5 kg/ha was used for seed inoculation. Inoculated plants gave significantly higher nodule number, nodule weight, stover yield and seed yield compared to uninoculated plants. Among four varieties, BARI Chola-3 produced the highest nodule number, nodule weight and stover yield, while the highest yield was obtained from BARI Chola-4. Key Words: Chickpea, Rhizobium, nodulation, yield. doi: 10.3329/bjar.v33i4.2287 Bangladesh J. Agril. Res. 33(4) : 549-554, December 2008